PENGARUH AKUNTABILITAS, KEPEMIMPINAN DAN PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PENGELOLAAN DANA DESA DI KOTA BANDA ACEH - Ayuandani, Kiki; Muniruddin, Said (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this study was to determine the effect of accountability, leadership and community participation on the effectiveness of village fund management in Banda Aceh City. The population is the Village Head and Village Treasurer in all gampongs in Banda Aceh totaling 90 Gampong with 180 respondents. In this study, the sample used was the entire population. Multiple linear regression test was used to test the research hypothesis. Simultaneous and partial research findings Accountability, Leadership and Community Participation affect the effectiveness of village fund management.